(untitled) (Western European Journal of Historical Events and Social Science, 2025)
This study explores the educational and socio-cultural integration of the Korean diaspora in the Surkhandarya region of Uzbekistan between 1937 and 1980, based primarily on archival sources. Drawing on materials from the Central State Archive of Uzbekistan and district-level archives of Sho‘rchi, Muzrabot, and Jarqo‘rg‘on, the research examines how Koreans— deported from the Russian Far East—adapted to new living conditions and became active participants in the region’s educational and cultural development